The Effect of Production and Consumption on Rice Price Inflation in the Province of North Sulawesi - Owen Dehoop; Stanny Rawung; Natalia Rumagit (Program Studi Ilmu Ekonomi, 2022)
The purpose of this study is (1) to determine the effect of production on rice price inflation in North Sulawesi province, (2) to determine the effect of consumption on rice price inflation in North Sulawesi province and (3) to determine the effect of production and consumption on rice price inflation. The method used in this study is a survey research method using Time Series analysis with the Eviews 9 software approach. The results of this study are (1) there is no positive effect of Production on Rice Price Inflation in North Sulawesi Province, (2) there is no positive influence of Consumption on Rice Price Inflation in North Sulawesi Province and (3) there is no positive influence of Production and Consumption together on Rice Price Inflation in North Sulawesi Province.